Tourism and sport orienteering as a national-regional component in the children physical education - Chechena Dazhy, Mira Balchirbay,; Mengi Saaya, Gulmira Mongush,; Saaya, Arat; Ayana Uvarova, Chechena Taryma, Sayana Kuzhuget, (Opción, 2019)
The paper considers methodological support implementation of elective education of the physical education program for 5-9 grade students of comprehensive secondary school on the basis of tourism and sport orienteering as national-regional component. A method of analyzing theoretical research study on the methodology of introducing tourism and sport orienteering in sports schools physical education of primary schools is used. Improvements and good changes in physical and technical-tactical preparedness and health condition of schoolchildren are revealed in a result of the experimental period. Research materials are useful for working out national-regional component content of school-thematic plans.